Respuesta :

OK, so to simplify the left hand side, we need to multiply -12 and -5 to get our final exponent for j, therefore we get j^60 = j^t,so t=60 is your answer

From the given equation value of [tex]'t'[/tex] is equals to [tex]60[/tex].

What is equation?

" Equation is defined as the algebraic expression which represents the relation between variables using sign of equality."

Formula used

[tex](a^{m} )^n= a^{mn}[/tex]

According to the question,

Given equation,

[tex](j^{-12})^{-5}=j^{t}[/tex]

Simplify given equation using formula we get,

[tex]j^{60}=j^{t}[/tex]

Equate the exponent with same base we get,

[tex]t= 60[/tex]

Hence , from the given equation value of [tex]'t'[/tex] is equals to [tex]60[/tex].

Learn more about equation from here

https://brainly.com/question/10413253

#SPJ3